'Eye Know': translating needs from annual health checks for people with learning disabilities to demand. (3rd February 2012) - Codling, Mary
<x xml:space="preserve">Abstract</x> Accessible summary When we evaluated our annual health checks, we found that many people with learning disabilities were not having their eyes checked. We wanted to find out why people with learning disabilities were not having their eyes tested. We worked with people with learning disabilities, their carers, families and optometrists to make eye checks more accessible for people with learning disabilities. The importance of this pilot study lies in the outcome, which shows that people with learning disabilities are now going to the optometrist and are having their eyes tested. Summary Annual health checks for people with learning disabilities are a concept that was introduced by the Government in 2001 as a catalyst to improve access to health services and identify health needs that have previously gone undetected. Nonetheless, to date, there has been little evidence of the effectiveness of these health checks. This study seeks to implore and share the findings from audits conducted on annual health checks in one geographical area that led us to translate consistent identified eye care needs and hence promoted the conception of a pilot study. The aim of this study was to understand the reasons why people with learning disabilities were not accessing optometrist and to amend current services with a view to increasing access and uptake of eye tests. The outcome has shown that access by people with learning disabilities to opticians has increased with a number of people having problems identified and glasses prescribed. This study provides an understanding of how evidence of consistent unmet need identified from annual health checks directed innovative practice to improve outcomes that are of benefit to people with learning disabilities. Annual health checks play a crucial role for people with learning disabilities and can provide the foundation for services to further explore why some health needs continue to go unmet.